Impact of compensation on employee performance with motivation as a moderator - Aryata, I Made; Marendra, I Gede (Jurnal Mantik, 2025)
PT. Securindo Packatama Indonesia (Secure Parking) is a company that provides parking services at various locations such as offices, hotels, shophouses, and hospitals. This study aims to examine the effect of compensation on employee performance with motivation as a moderating variable. Using a quantitative approach with the Structural Equation Modeling (SEM) method and involving 40 respondents, the research included tests for normality, validity, reliability, moderation, hypothesis, and goodness of fit. The normality test showed a multivariate value of 0.356 (<2.58), the second-stage validity test confirmed all indicators were valid (estimate >0.50), and the reliability test indicated sufficient reliability with CR >0.70 and AVE >0.50. However, hypothesis testing showed that compensation had no significant effect on performance (p = 0.922), motivation also had no significant effect (p = 0.155), and motivation did not moderate the effect of compensation on performance (p = 0.488). Therefore, it is necessary to explore other variables that may be more relevant in improving employee performance.